2020
DOI: 10.1016/j.athoracsur.2020.03.084
|View full text |Cite|
|
Sign up to set email alerts
|

Early Versus Late Rib Fixation in Patients With Traumatic Rib Fractures: A Nationwide Study

Abstract: Background. The appropriate timing of rib fixation remains unclear. We investigated the efficacy of early rib fixation compared with late rib fixation, using data from a Japanese nationwide inpatient database.Methods. We identified patients who underwent rib fixation and received mechanical ventilation from July 1, 2010, to March 31, 2018, using data from the Diagnosis Procedure Combination database in Japan. The primary outcome was the duration of mechanical ventilation after rib fixation. Secondary outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…While only the first study was available at the time of developing these guidelines, the more recently published studies corroborate this consensus of early SSRF benefit (75,(78)(79)(80)(82)(83)(84)89). In addition, early SSRF appears to be safe and also beneficial in elderly patients for all outcomes and is associated with lower hospitalization costs (80,83,84). Interestingly, recent studies have also suggested that while early fixation within 2-3 days after admission is associated with improved in-hospital outcomes, performing SSRF after this time period might actually correlate with outcomes inferior to nonoperative management (81,82).…”
Section: Commentsmentioning
confidence: 90%
See 2 more Smart Citations
“…While only the first study was available at the time of developing these guidelines, the more recently published studies corroborate this consensus of early SSRF benefit (75,(78)(79)(80)(82)(83)(84)89). In addition, early SSRF appears to be safe and also beneficial in elderly patients for all outcomes and is associated with lower hospitalization costs (80,83,84). Interestingly, recent studies have also suggested that while early fixation within 2-3 days after admission is associated with improved in-hospital outcomes, performing SSRF after this time period might actually correlate with outcomes inferior to nonoperative management (81,82).…”
Section: Commentsmentioning
confidence: 90%
“…The next study was a retrospective national database study of the same time period and patient population as the previous study (83). In this study (n=211), patients who underwent SSRF were stratified based on the median time to SSRF in ≤6 and >6 days (no range given) following admission.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Majak and Naess stated that SSRF within the first 72 h might lead to a better outcome ( 28 ). The Japanese group around Otaka was able to demonstrate an association of a better in-hospital outcome for early surgical fixations, whereas later surgical fixation was not ( 29 , 30 ). The first review article discussing early vs. late SSRF was published by Radomski and Pieracci in 2019, stating that an early SSRF within 72 h should be achieved but was only based on three publications at this point of time ( 31 ).…”
Section: Discussionmentioning
confidence: 97%
“…The timing of surgical stabilization in patients with thoracic trauma also seems to have a relevant influence on the clinical outcome. A study published in 2020 by Otaka et al reported significant reductions in the duration of mechanical ventilation, the duration of hospitalization and economic expenses, provided that the rib stabilization took place a maximum of 6 days after the accident occurred ( 23 ).…”
Section: Discussionmentioning
confidence: 99%